THE STATE OF THE ORGANIZATION OF BEAUTIFICATION IN UKRAINE IN THE CONTEXT OF PUBLIC HEALTH IMPACT: UPDATE OF PUBLIC POLICY - Demikhov O. І. (Pressing Problems of Public Administration, 2021)
The role of settlements and large cities is constantly growing in the progress of society. Beautification creates a habitable environment in the settlement, stimulates the preservation and reproduction of community health. Local authorities must strategically plan beautifications activities. The study of such public policy is extremely relevant. Scientists pay great attention to the management of beautification in settlements. Thus, O. Ignatenko in his works [3; 4] studies the issues of state regulation of beautification and control system. Also, researchers O. Ignatenko, G. Marushevsky and O. Ryabukha analyze the field of ecology of the city and propose optimization strategies [5]. I. Solonnikova studies the formation of the policy of improvement of settlements [21]. The connection between public health and urban development has not yet been sufficiently studied. The purpose of the article is to determine the state of beautification in Ukraine and its connection with public health, to identify problems of such state and local public policy. The planet’s population is growing rapidly and most of the population lives in cities. The situation is similar in Ukraine. The pace of urbanization in Ukraine exceeds the capacity of local governments to develop urban infrastructure. It causes problems in the quality of life and health of the community. High living density creates a man-made load on nature. Problems of waste utilization are intensifying. Therefore, modern territorial management must be based on the principles of a single ecosystem. The Government of Ukraine states that the level of beautification in the country is not high. There is a disorder in the organization of burials; low quality of the road network; etc. Public involvement in beautification management is also important. In this way, the culture of public health is spreading. Health culture, public health and beautification are closely linked. The author is convinced that the culture of community health is a key element of the new public policy of community management. The analysis of the state of public works and public health in modern Ukraine has identified the following problems: imperfect arrangement of storm sewer systems and centralized drainage; low quality of the road network of settlements; insufficient number of playgrounds and sports grounds, etc. State and local public policies need to be improved: preparing society and the economy for population aging; development of a strategy and program for local development, taking into account the relationship between beautification and public health; actively informing the population about the impact of landscaping on the health of the community; introduce cremation and bioburial; actively involve community members in local management of beautification; to strengthen the role of beautification inspections in settlements, etc.